Segni, ferite, animali e figure: su Libri e contro il tarlo inimico di Roberto Roversi (2012) - Portesine, Chiara (L'ospite ingrato, 2024)
This article aims to critically examine Libri e contro il tarlo inimico (2012), a collection of seventy poems dedicated to the theme of reading and libraries (both private and public). First, cases of the “animalization” of the book as an object, often compared by Roversi to domestic or wild animals, will be identified and analyzed. In addition to these metaphorical bestiaries, the analysis focuses on the iconographic apparatus, with a specific focus on Tre invettive contro il tarlo, nemico del libro, an artist’s book published in 1997 that includes three poems by Roversi and an engraving by Romano Masoni.